AMS02 positron excess from decaying fermion DM with local dark gauge symmetry - P. Ko; Yong Tang (Physics Letters B, 2015)
Positron excess observed by PAMELA, Fermi and AMS02 may be due to dark matter (DM) pair annihilation or decay dominantly into muons. In this paper, we consider a scenario with thermal fermionic DM (χ) with mass ∼O(1–2) TeV decaying into a dark Higgs (ϕ) and an active neutrino (νa) instead of the SM Higgs boson and νa. We first present a renormalizable model for this scenario with local dark U(1)X gauge symmetry, in which the DM χ can be thermalized by Higgs portal and the gauge kinetic mixing. Assuming the dark Higgs (ϕ) mass is in the range 2mμ<mϕ<2mπ0, the positron excess can be fit if a proper background model is used, without conflict with constraints from antiproton and gamma-ray fluxes or direct detection experiments. Also, having such a light dark Higgs, the self-interaction of DM can be enhanced to some extent, and three puzzles in the CDM paradigm can be somewhat relaxed.